An enzyme-free biosensor for sensitive detection of Salmonella using curcumin as signal reporter and click chemistry for signal amplification - Huang, Fengchun (Theranostics, 2018)
In this study, an enzyme-free biosensor was developed for sensitive and specific detection of Salmonella typhimurium (S. typhimurium) using curcumin (CUR) as signal reporter and 1,2,4,5-tetrazine (Tz)-trans-cyclooctene (TCO) click chemistry for signal amplification. Methods: Nanoparticles composed of CUR and bovine serum albumin (BSA) were formulated and reacted with Tz and TCO to form Tz-TCO-CUR conjugates through Tz-TCO click chemistry. Then, the Tz-TCO-CUR conjugates were functionalized with polyclonal antibodies (pAbs) against S. typhimurium to form CUR-TCO-Tz-pAb conjugates. Magnetic nanoparticles (MNPs) conjugated with monoclonal antibodies (mAbs) against S. typhimurium through streptavidin-biotin binding were used to specifically and efficiently separate S. typhimurium from the background by magnetic separation. CUR-TCO-Tz-pAb conjugates were reacted with the magnetic bacteria to form CUR-Tz-TCO bacteria. Finally, CUR was released quickly from the CUR-Tz-TCO bacteria in the presence of NaOH, and the color change was measured at the characteristic wavelength of 468 nm for bacteria quantification. Results: A linear relationship between absorbance at 468 nm and concentration of S. typhimurium from 102 to 106 CFU/mL was found. The lower detection limit was calculated to be as low as 50 CFU/mL and the mean recovery was 107.47% for S. typhimurium in spiked chicken samples. Conclusion: This biosensor has the potential for practical applications in the detection of foodborne pathogens.